Parenting Across Broken Marriages: A Socio-Legal Analysis of Custody and Child Welfare in India (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The dissolution of marriage is not merely the legal termination of a marital relationship but also a profound social transition that significantly impacts parenting, custody arrangements, and child welfare. In India, where family values and collectivist traditions remain deeply entrenched, divorce or marital breakdown carries additional complexities beyond emotional distress, including social stigma, financial instability, and the redefinition of parental responsibilities. This article undertakes a socio-legal analysis of custody and child welfare within the Indian context, tracing the historical evolution of custody laws from colonial to contemporary statutes, and analysing the judicial interpretations that shape the rights of parents and the best interests of the child. It explores the challenges faced by parents in broken marriages, including legal disputes, gendered expectations, and the role of extended families in caregiving. It also examines the psychological and social implications of custody decisions on children, highlighting issues of adjustment, stability, and identity formation. Finally, the article assesses the current legal framework governing custody and guardianship under statutes such as the Hindu Minority and Guardianship Act, 1956, and the Guardians and Wards Act, 1890, alongside international conventions. It concludes by identifying gaps in the present system and suggesting reforms that prioritize child welfare, promote shared parenting, and balance the interests of both parents.